The Role of mTOR Inhibitors in Hematologic Disease: From Bench to Bedside - Feng, Yimei; Chen, Xiaoli; Cassady, Kaniel; Zou, Zhongmin; Yang, Shijie; Wang, Zheng; Zhang, Xi (Frontiers in Oncology, 2021)
The mTOR pathway plays a central role in many cellular processes, such as cellular growth, protein synthesis, glucose and lipid metabolism. Aberrant regulation of mTOR is a hallmark of many cancers, including hematological malignancies. mTOR inhibitors, such as Rapamycin and Rapamycin analogs (Rapalogs), have become a promising class of agents to treat malignant blood diseases – either alone or in combination with other treatment regimens. This review highlights the mechanistic underpinnings of mTOR inhibitors, as assayed in basic research, to their evolving role in the treatment of hematologic disease, including leukemia, lymphoma, myeloma, immune hemocytopenia, and graft-versus-host disease (GVHD). Based on data presented in this review, we believe that mTOR inhibitors are becoming a trusted resource in the clinical hematologist’s toolbelt and should be considered more routinely in combination therapy for the management of hematologic disease.